Correspondence of Florence O’Donoghue with Éamon De Valera's secretary regarding the unveiling of a memorial to Cork No. 1 Brigade at St. Finbar’s Cemetery on 17th Nov. 1963 and regarding Countess Markieviez’s prayerbook, presented to the Kilmainham Jail Restoration Committee, - O'Donoghue, Florence, 1895-1967 (1963)
Correspondents include various members of Éamon De Valera's staff.